Goat reproductive performance as affected by stocking rate on caatinga vegetation - Filho, Clovis Guimarães; Góes, José Givaldo Givaldo (Pesquisa Agropecuaria Brasileira, 2014)
This study was aimed at determining the influence of native goats grazing caatinga under different stocking rates on production either per animal or per unit area. Ninety does were allocated by stratified randomization, on the basis of liveweight, into three treatments with two replications of each. Stocking rates applied were: 3.0 ha (low), 2.0 ha (moderate), and 1,0 ha per doe (high). Measurements were performed over three periods of observation: 1981-82 (I), 1982-83 (II), and 1983-84 (III). Kids were removed from the plots at weaning (112 days). Does were continuously exposed for mating throughout the three-year experimental period. Results showed no evidence of any effect (P >0.05) of stocking rate on either fertility or fecundity. Mean values for kids weaned per kid born were also similar (P <0.05) for all treatment groups. Number of kids weaned per doe exposed increased (P <0.05) with decrease in stocking rates. At the low stocking rate 77% more kids were weaned than at the high one. When performance was expressed per unit area of land, 70% more kids (P <0.05) were weaned at the high stocking group than at the low one. Data indicate that stocking similar caatinga at rates ranging from one to three hectares per doe does not show marked differences in fertility of fecundity, but it does show in weaning rates both per doe and per unit area.